2007
DOI: 10.1002/chem.200600899
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalysts on Alkaline‐Earth Supports for Racemization and Dynamic Kinetic Resolution of Benzylic Amines

Abstract: Palladium catalysts on alkaline-earth supports were studied as new heterogeneous catalysts for racemization of chiral benzylic amines such as 1-phenylethylamine. Particularly 5 % Pd/BaSO(4) and 5 % Pd/CaCO(3) were able to selectively racemize amines, with minimal formation of secondary amines or hydrogenolysis to ethylbenzene. In contrast, these side reactions were pronounced on Pd/C. A reaction mechanism is proposed that is consistent with the reaction kinetics. The catalyst activity was found to depend on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 36 publications
3
66
0
9
Order By: Relevance
“…The Ru(OH) x /TiO 2 (A) catalyst showed the highest TOF, more than sixteen times higher than those of heterogeneous catalysts, [10] ). [2, 10h] Moreover, the TOF reached up to 1061 h À1 when the racemization of (R)-1-phenylethanol was carried out with 0.5 mol % of Ru(OH) x /TiO 2 (A) at 373 K [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ru(OH) x /TiO 2 (A) catalyst showed the highest TOF, more than sixteen times higher than those of heterogeneous catalysts, [10] ). [2, 10h] Moreover, the TOF reached up to 1061 h À1 when the racemization of (R)-1-phenylethanol was carried out with 0.5 mol % of Ru(OH) x /TiO 2 (A) at 373 K [Eq.…”
Section: Resultsmentioning
confidence: 99%
“…[7] Although many efficient methods for homogeneous hydrogen-transfer reactions catalyzed by transitionmetal complexes have been developed, [7][8][9] these systems often need additives such as hydrogen acceptors or bases to promote the reactions and have the above-mentioned disadvantages, namely, the difficulty of catalyst/product(s) separation and reuse of catalysts. To the best of our knowledge, there are few examples of the heterogeneously catalyzed racemization of alcohols and amines [2,10] and only one example of the selective reduction of allylic alcohols with an alcohol as the hydrogen source. [3] We prepared three kinds of supported ruthenium hydroxide catalysts with different TiO 2 supports: Ru(OH) x / TiO 2 (A), Ru(OH) x /TiO 2 (B), and Ru(OH) x /TiO 2 (C) (see later section), and these catalysts could act as efficient, reusable heterogeneous catalysts for various hydrogen-transfer reactions, such as the racemization of chiral secondary alcohols [Eq.…”
Section: Introductionmentioning
confidence: 98%
“…Although the non-benzylic amines 3e-f (Table 2) are not vulnerable to these benzylic carbon-nitrogen degradation pathways, they are nonetheless susceptible to racemization events at high temperature over prolonged reaction times. [24] Finally, to push the limits of the developed method, we subjected ketone 1b to a one-pot reductive amination-hydrogenolysis-reductive amination sequence, five reactions in total, forming diamine 4 in 58% yield (from 1b) in > 99% ee (Scheme 4, top). In this sequence, the second reductive amination consumed 2-pyridinecarboxaldehyde, which was added after primary amine 3b had fully accumulated (GC analysis).…”
Section: Resultsmentioning
confidence: 99%
“…They found that palladium particles dispersed on alkaline earth salts such as BaSO 4 , CaCO 3 , and SrCO 3 are active for the racemization of benzylic amines. [58] They suggested that the racemization proceeds through dehydrogenation and hydrogenation, and that the main role of the basic supports is suppression of the condensation of the substrate amine and the intermediate imine. Pd/BaSO 4 (18) was the best for the DKR of 1-phenylethylamine.…”
Section: Racemization Catalysts and Reaction Conditions For Dkr Of Ammentioning
confidence: 99%
“…Since Reetz and Schimossek [6] reported the use of palladium on charcoal (17) for DKR of amines, several heterogeneous catalysts on varying supporting materials have been introduced for racemization of amines (Table 9). [58][59][60][61][62] The Shvo-type ruthenium complexes 1 [63,64] and the iridium complex 21 [65,66] are unusual examples of homogeneous ones.…”
Section: Racemization Catalysts and Reaction Conditions For Dkr Of Ammentioning
confidence: 99%